The Planned Alternating Pathways: a flexible protocol for working with anorexic and bulimic adolescents and their families - Ugazio, Valeria; Fellin, Lisa Chiara (Frontiers in Psychology, 2025)
The article presents the Planned Alternating Pathways, a flexible systemic protocol structured into four phases for working with adolescent with anorexia and bulimia and their families. Largely inspired by the Family Semantic Polarity Theory, it maintains the assumption of pioneering systemic approaches that anorexia and bulimia are coping strategies, albeit very dangerous. The protocol aims to empower the family as a whole. Its main purpose is to change the positions of the patient and the family members who feel and/or are considered to be at a disadvantage, while reducing internal competition and polarization between so-called “winners” and “losers.” These are particularly harsh in families with eating disorders, where the semantic of power generally prevails. The protocol places tailored psychotherapy at its centre and revolves around three main objectives: (1) to maximise the generally fragile therapeutic alliance with the family and above all with the patient; (2) to lengthen the treatment; 3) to overcome a typical therapeutic dilemma of eating disorders concerning the duration of the treatment. The psychotherapeutic process should be long enough to address the identity issues of the patient with anorexia or bulimia, but as soon as the patient regains a normal or near-normal weight, parents drop out therapy or put the therapeutic team in the position of terminating it. The introduction of an individual phase helps to prevent this too early conclusion of treatment and distinguishes the format from that of traditional family therapy. The individual path approaches the patient’s emotions, feelings and moods in an indirect way, while helping the patient to discover her hidden talent, often suppressed by “competitive trails.” This phase also paves the way for a possible return to therapy, should existential issues arise in the future. The protocol can be extended to the treatment of adolescents or young adults with other problems and disorders, because it takes into account the changes that have occurred in all families that make it difficult long-term involvement of the whole family in the therapeutic experience. It also enhances the family’s resources while reduces the asymmetry between patients and therapists increasingly unpalatable in Western societies.